Training of educators in environmental education: The site as a digital resource for teaching and socio-environmental organization (Research, Society and Development, 2023)
The article is an excerpt from the professional doctorate thesis in Science teaching at the Federal Institute of Rio de Janeiro. The objective is to awaken, expanding the ideological and subjective conceptions of the subjects, mediated by TDIC as a resource for socio-environmental (self) formation, with the creation of a website. We adopted participant-action research with unstructured participant observation, based on Novaes and Gil, with questionnaires applied to students specializing in Teaching for Technical Professional Education, as evaluators of the website in the first instance as the Educational Product of the thesis. The website organized doctoral research and two extension courses in distance learning, with the proposal to mainstream Critical Environmental Education, linked to the educational curriculum of Basic and Professional Technical Education. For the evaluation of the website, we mainly describe in this article the validation in the second instance, carried out by peer reviewers, composed of doctors, with training in the areas of education, science teaching and technology. In the results and discussion, Barbosa contributed to carrying out the interpretative analysis of the context, based on questionnaires from course participants in 2022 and judges in 2023, where we improved the website as a digital resource for teaching, organization and socio-environmental dissemination. As final considerations, the work responds to the research problem, in describing how TDIC collaborate with the performance of the contemporary Educator in different training processes, starting from transversal themes for Critical Environmental Education, considering the real context problems.